A Randomized Trial of Topical Epinephrine and Rectal Indomethacin for Preventing Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis in High-Risk Patients. (February 2019) - Kamal, Ayesha; Akshintala, Venkata S.; Talukdar, Rupjyoti; Goenka, Mahesh K.; Kochhar, Rakesh; Lakhtakia, Sundeep; Ramchandani, Mohan K.; Sinha, Saroj; Goud, Rajesh; Rai, Vijay K.; Tandan, Manu; Gupta, Rajesh; et al.
Abstract : INTRODUCTION: Rectal indomethacin and topical spray of epinephrine have separately shown efficacy in the prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP) in randomized controlled trials. We hypothesized that the combination of indomethacin and topical spray of epinephrine on the duodenal papillae would further reduce PEP than when indomethacin was used alone. Methods: We conducted a comparative effectiveness, multicenter, double-blinded, randomized trial of rectal indomethacin alone vs a combination of rectal indomethacin and topical spray of epinephrine for the prevention of PEP in high-risk patients. The primary outcome was the incidence of PEP and the secondary outcome was the severity of PEP. A 2-tailed Fisher's exact test was used to analyze the difference in the proportion of patients with PEP in the indomethacin alone vs the combination group. Results: A total of 960 patients (mean age 52.33 ± 14.96 years; 551 [57.4%] females) were randomized and 959 completed follow-up. The baseline demographic and clinical characteristics were similar between the 2 groups. Women <50 years of age (25.4%) and difficult cannulation (84.9%) were the most common PEP risk factors. The incidence of PEP was 6.4% in the indomethacin alone group (n = 482) compared to 6.7% in the combination group (n = 477; P = 0.87). Severe PEP was found in 5 (12%) and 7 (16%) patients in the indomethacin alone and combination groups, respectively ( P = 0.88). The overall mortality was 0.6%, which was unrelated to the primary outcome. Conclusions: The combination of rectal indomethacin and topical spray of epinephrine does not reduce the incidence of PEP compared to rectal indomethacin alone in high-risk patients; https://clinicaltrials.gov/ct2/show/NCT02116309 .